Kecepatan Membaca Arab Melayu Kelas 2023B Dalam Cerita “Lebai Malang” - Diah Hananda Lumbanraja; Regina Okto Haryati; Ilma Putri Yeniza; Hasnah Faizah (PT. ALHAFI BERKAH INDONESIA, 2023)
Malay Arabic is writing that uses Arabic writing, especially the Hijaiyah letters, through the medium of the Malay language. The emergence of Malay Arabic writing is in line with the development of Islam in the Malay region, then introduced by great scholars who spread Islam through Arabic writing in Malay. If Latin letters are read from left to right then, Malay Arabic letters are read from right to left. The methodology used in the research is descriptive method. The object of this research is the ability to read Malay Arabic writing, while the subject is Indonesian Language and Literature Education Class 2023 Class B FKIP Riau University students. The data analysis technique uses quantitative data analysis. Aims to analyze the data obtained in the field, namely the Malay Arabic reading speed test by reading one story. Reader speed is taken to measure how fast 2023B students are in reading paragraphs in Hasnah Faizah's Malay Arabic storybook, entitled